2020
DOI: 10.5713/ajas.19.0004
|View full text |Cite
|
Sign up to set email alerts
|

Effects of puerarin on the Akt signaling pathway in bovine preadipocyte differentiation

Abstract: Objective: Puerarin has the potential of regulating the differentiation of preadipocytes, but its mechanism of action has not yet been elucidated. Adipocytes found in adipose tissue, the main endocrine organ, are the main sites of lipid deposition, and are widely used as a cell model in the study of in vitro fat deposition. This study aimed to investigate the effects of puerarin on adipogenesis in vitro. Methods: Puerarin was added to the culture medium during the process of adipogenesis. The proliferation and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Though many studies mentioned the negative effect of puerarin on fat deposition in animals (Jung et al., 2017; Zheng et al., 2015), some studies of in vitro also found that supplementation with puerarin benefited synthesis of lipid. One recently study by Yun et al., (2020) reported that puerarin promotes the differentiation of preadipocytes and improves adipogenesis of Yan Yellow cattle in vitro; consistently, another report by Lee et al., (2010) showed that puerarin upregulates mRNA expression of PPARγ and enhances adipocyte differentiation, adiponectin expression, and antioxidant response in 3T3‐L1 cells. And meanwhile, the results in the present study showed that the puerarin treatment by 400 mg/kg increased the intramuscular fat of beef cattle.…”
Section: Discussionmentioning
confidence: 89%
“…Though many studies mentioned the negative effect of puerarin on fat deposition in animals (Jung et al., 2017; Zheng et al., 2015), some studies of in vitro also found that supplementation with puerarin benefited synthesis of lipid. One recently study by Yun et al., (2020) reported that puerarin promotes the differentiation of preadipocytes and improves adipogenesis of Yan Yellow cattle in vitro; consistently, another report by Lee et al., (2010) showed that puerarin upregulates mRNA expression of PPARγ and enhances adipocyte differentiation, adiponectin expression, and antioxidant response in 3T3‐L1 cells. And meanwhile, the results in the present study showed that the puerarin treatment by 400 mg/kg increased the intramuscular fat of beef cattle.…”
Section: Discussionmentioning
confidence: 89%
“…Finally, the enrichment analysis of the genes regulated and containing eQTL associated with IMF revealed that those genes were involved in signal transduction, cell cycle, and development pathways, like the AKT signaling ( Figure 5A ). The AKT or PI3K-AKT signaling is an intracellular pathway essential for signal transduction, cell proliferation, apoptosis, and metabolism ( Yun et al, 2020 ). Furthermore, AKT plays a crucial role in adipocyte differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, AKT plays a crucial role in adipocyte differentiation. AKT can drive fat production and promote adipogenesis through phosphorylation of substrates, such as Fox family members ( Kim et al, 2010 ; Wang et al, 2020 ; Yun et al, 2020 ). Corroborating these findings, in the current study, the FOXO3 TF, negatively regulated by the 21:22425675 eQTL, was enriched for the Signal transduction AKT signaling.…”
Section: Discussionmentioning
confidence: 99%
“…The adipogenic cocktail applied to the preadipocytes simulates this condition. While dexamethasone inhibits mitochondrial respiration (Pandya et al, 2007), IBMX, insulin, thyronine, pioglitazone, and transferrin promote Akt (also known as protein kinase B) activation (Yun et al, 2019) and translocation of glucose transporters to the plasma membrane. The fact that pioglitazone promotes Akt activation even under insulin resistance (Yang et al, 2017) is important, because the preadipocytes were isolated from obese people with probable insulin resistance.…”
Section: Discussionmentioning
confidence: 99%